Towards a unified framework for integrating plant biologicals into soil health management - Svend Christensen; Mette Haubjerg Nicolaisen; Anne Winding; Helle Hestbjerg; Mette Walter; Rasmus Emil Jensen; MeiLee Ling; Cristine Morgan; Veronika Hansen (Plant and Soil, 2026)
Plant biologicals are a widely used yet loosely defined term that generally refers to products intended to enhance plant growth, productivity, and protection against pests and diseases. Many, such as microbial inoculants, biostimulants, and plant-derived compounds, also influence microbial communities and processes. The functionality has been recognised for decades, but consistent field-level benefits remain difficult to demonstrate. Advances in formulation and monitoring now offer renewed opportunities to apply biologicals more effectively as tools for managing soil biological processes. They are increasingly recognised for their capacity to influence microbial diversity, stimulate enzymatic activity, and promote nutrient cycling—processes central to soil health. Broader adoption, however, is constrained by unclear definitions of soil health-related effects, lack of harmonised indicators, inconsistent field-testing, and regulatory frameworks misaligned with the characteristics of biological inputs. Drawing on insights from the 2025 Plant Biologicals Network (PBN) workshop on soil health, the opinion paper reviews the current evidence base and key research gaps, highlighting that efficacy remains highly context-dependent and long-term legacy effects are poorly understood. We emphasise the need for emerging technologies and digital tools, including molecular diagnostics, biosensors, and machine learning approaches, that can provide scalable, high-resolution insights into microbial dynamics and soil processes. Finally, we outline a coordinated research and innovation agenda that prioritises harmonised indicators, long-term comparative field measurements, and incentive-aligned frameworks. By integrating scientific, technological, and institutional advances, plant biologicals can evolve from crop-enhancing inputs into credible and scalable instruments for managing soil processes within sustainable soil health strategies.